The Effect of Fear of Missing Out (FOMO) Based on Social Media Promotional Content on Consumer Purchase Decisions: A Case Study of Durian Pancakes in Talang Durian Tebang, Bengkulu City - Heskyel Pranata Tarigan; Fitri Kofifah (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the effect of Fear of Missing Out (FOMO) based on social media promotional content on consumer purchasing decisions at Pancake Durian Talang Durian Tebang Store in Bengkulu City. The FOMO phenomenon, increasingly prevalent in the digital era, drives consumers to make purchasing decisions influenced by viral content on social media platforms such as Instagram, TikTok, and Facebook. The research method used is a quantitative approach with simple linear regression analysis. The research sample consisted of 100 respondents who are active consumers of the store, selected using purposive sampling technique. Data collection was conducted through a questionnaire with a Likert scale (1–5). The results show that FOMO based on social media promotional content has a positive and significant effect on consumer purchasing decisions with a coefficient of determination (R²) of 0.612, meaning that 61.2% of the variation in purchasing decisions can be explained by the FOMO variable. The t-test produced a t-count value of 12.534 > t-table 1.984 with a significance of 0.000 < 0.05, so the alternative hypothesis is accepted.